Early Versus Delayed Laparoscopic Cholecystectomyafter Endoscopic Retrograde Cholangio-Pancreatography (ERCP) Removal of Choledocholithiasis: An Evidence-based Case Report - Firman, Fauzan Hertrisno; Harianja, Gerald Abraham; Maulahela, Hasan (The Indonesian Society for Digestive Endoscopy, 2022)
Aim: To determine the preferred method of treatment in patients with choledocholithiasis after endoscopic retrograde cholangiopancreatography (ERCP) by evaluating efficacy of early laparascopic cholecystectomy compared to delayed laparoscopic cholecystectomy.Method: Literature searching was carried out on two databases, PubMed and Cochrane, according to the inclusion and exclusion criteria. Two randomized clinical trial (RCT) studies were appraised critically for validity, importance, and applicability.Results: Early laparascopic cholecystectomy after ERCP shows lower outcomes in incidence of recurrent choledocholithiasis, acute cholecystitis, duration of hospitalization, and treatment costs (p 0.05). Meanwhile, there was no significant difference (p 0.05) between the two groups regarding the incidence of biliary adhesions, bleeding during cholecystectomy, and laboratory parameters such as total bilirubin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and gamma glutamyl transferase (GGT).Conclusion: Early cholecystectomy, within three days after ERCP, is recommended for the treatment of choledocholithiasis after ERCP removal.